Primal branding create zealots for your brand, your company, and your future - Hanlon, Patrick (Free Press, 2006)
"In one of the most original books of its kind ever written, Patrick Hanlon explains how the most powerful brands create a community of believers around the brand, revealing the seven components that will help every company and marketer capture the public imagination - and seize a bigger slice of the pie." "In Primal branding, Hanlon explores those seven components, known as the primal code, and shows how to use and combine them to create a community of believers in which the consumer develops a powerful emotional attachment to the brand. These techniques work for everyone involved in creating and selling an image - from marketing managers to social advocates to business leaders seeking to increase customer preference for new or existing products. Primal branding presents a world of new possibility for everyone trying to spark public appeal - and the opportunity to move from being just another product on the shelf to becoming a desired and necessary part of the culture."--BOOK JACKET.